2009
DOI: 10.1681/asn.2008101037
|View full text |Cite
|
Sign up to set email alerts
|

Daclizumab versus Antithymocyte Globulin in High-Immunological-Risk Renal Transplant Recipients

Abstract: Nondepleting anti-CD25 monoclonal antibodies (daclizumab) and depleting polyclonal antithymocyte globulin (Thymoglobulin) both prevent acute rejection, but these therapies have not been directly compared in a high-risk, HLA-sensitized renal transplant population. We randomly assigned 227 patients, who were about to receive a kidney graft from a deceased donor, to either Thymoglobulin or daclizumab if they met one of the following risk factors: current panel reactive antibodies (PRA) Ͼ30%; peak PRA Ͼ50%; loss o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
161
3
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(175 citation statements)
references
References 23 publications
6
161
3
5
Order By: Relevance
“…1,2 In such patients, benefits likely overcome the increase in the risk of CVEs. However, in our view, these patients should be considered at very high risk of cardiovascular complications and taken over in this way.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 In such patients, benefits likely overcome the increase in the risk of CVEs. However, in our view, these patients should be considered at very high risk of cardiovascular complications and taken over in this way.…”
Section: Discussionmentioning
confidence: 99%
“…ATGs have potent immunosuppressive properties and have been proven to be superior to anti-CD25 mAb in immunologic highrisk patients. 1,2 These polyclonal antibodies are a complex mixture of antibodies with multiple specificities directed against both T and non-T cells. 1,2 They produce profound T-cell depletion 1,2 and induce persistent changes in T-cell subsets characterized by a low…”
mentioning
confidence: 99%
“…48 In practice, ATG should be preferred in sensitized patients without DSAs, because two randomized clinical trials showed beneficial short-term effects on acute rejection, graft function, and survival (however, the relationship between induction immunosuppression, dnDSAs, and AMR was not specifically addressed). 49,50 In a more recent trial, Brokhof et al 51 reported in a cohort of 114 moderately sensitized recipients of deceased donor renal transplants that induction with ATG is associated with a reduction in the occurrence of dnDSAs and AMR compared with basiliximab. However, it should be noted that, in this study, (1) the difference became statistically different only at 3 years, (2) only a few patients assigned to basiliximab had a follow-up at 36 months, and (3) the patients who received ATG also received more plasmapheresis and IVIg than the patients who received rituximab.…”
Section: Effect Of Induction Therapy On Dndsa Generationmentioning
confidence: 99%
“…This advantage was also seen among highly sensitized and 'high risk' recipients, making ATG the induction therapy of choice in such patients [36,37]. Therefore, considering the adverse effect profi le of ATG, it is mostly reserved for transplants categorized as 'high risk' of early rejection [5].…”
Section: Causes Actual Lysis Of T Cells and Their Destructionmentioning
confidence: 99%